2012
DOI: 10.5194/angeo-30-259-2012
|View full text |Cite
|
Sign up to set email alerts
|

Features of the seasonal variation of the semidiurnal, terdiurnal and 6-h components of ozone heating evaluated from Aura/MLS observations

Abstract: Abstract. This paper presents the thermal forcing of the semidiurnal, terdiurnal, and 6-h components of the migrating tide induced by ozone heating in stratosphere and lower mesosphere. The heating as a function of local time is determined from the global ozone observed by the Microwave Limb Sounder on the Aura satellite. The harmonic components of the heating rates of the semidiurnal, terdiurnal and the 6-h periodicities are calculated using the Strobel/Zhu parameterized model and then decomposed into Hough m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 26 publications
1
35
0
1
Order By: Relevance
“…[30] The Hough modes from the classical tidal theory are orthogonal and complete covering from pole to pole [Xu et al, 2012]. However, in this paper, it should be pointed out that the stations of the IGGCAS meteor radar chain locate at the middle-and low-latitudes in the Northern Hemisphere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30] The Hough modes from the classical tidal theory are orthogonal and complete covering from pole to pole [Xu et al, 2012]. However, in this paper, it should be pointed out that the stations of the IGGCAS meteor radar chain locate at the middle-and low-latitudes in the Northern Hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the space-borne observations, such as the Wind Imaging Interferometer and High Resolution Doppler Imager on board the UARS, and the TIMED Doppler Interferometer on board the Thermosphere-Ionosphere-Mesosphere Energetic and Dynamics (TIMED) spacecraft, revealed a wealth of information on the global structure of upper atmospheric tides [Manson et al, 2002a;Oberheide et al, 2006Oberheide et al, , 2007Pancheva et al, 2009b;Shepherd et al, 1999;Wu et al, 2006]. Owing to the virtue of their global coverage, they are capable of providing both the latitudinal and longitudinal structures of any tides from the space-borne measurements; this makes it possible to distinguish the migrating and nonmigrating tides and to decompose different Hough modes Lu, 2008a, 2008b;Mukhtarov et al, 2009;Xu et al, 2012;Xu et al, 2011;Zhang et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al . () showed that the symmetric mode of semidiurnal stratospheric ozone heating minimizes in June–July (see their Fig. 11).…”
Section: Seasonal Cycle Of S1(p) and S2(p)mentioning
confidence: 97%
“…The smaller A 2 in boreal summer vs. winter is understandable largely as a consequence of the eccentricity of the Earth's orbit -the Sun-Earth distance is over 3% shorter at perihelion (in early January) than at aphelion (in early July) resulting in nearly 7% annual modulation of the effective solar flux reaching the top of the atmosphere. Xu et al (2012) showed that the symmetric mode of semidiurnal stratospheric ozone heating minimizes in June-July (see their Fig. 11).…”
Section: Introductionmentioning
confidence: 94%
“…The symmetric modes are (1, 1), (1, 3), (1, 5), (1, 7)… and (1, À2), (1, À4), (1, À6), (1, À8)…, while the antisymmetric modes are represented by (1, À1), (1, À3), (1, À5), (1, À7)… and (1, 2), (1, 4), (1, 6), (1, 8)…. Hough functions are useful for expansion of tidal fields (e.g., Φ in equation (2)) to investigate their latitudinal distribution and vertical propagation [Zurek, 1976;McLandress, 2002c;Takahashi et al, 2006], and the thermal heating (J in equation (3)) of various atmospheric compositions to estimate their effects in tidal excitation [Lindzen, 1968;McLandress, 2002c;Xu et al, 2012]. In the next section, we use the 16 sets of Hough functions shown in Figure 1 to decompose MDT extracted from MCS temperature field to explore their composition characteristics and the seasonal variations.…”
Section: Hough Functionsmentioning
confidence: 99%